2016
DOI: 10.1177/107327481602300110
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia in 2 Patients Receiving Palbociclib for Breast Cancer

Abstract: The authors reviewed retrospective cases of 2 women - one aged 78 years and the other aged 86 years - with estrogen receptor (ER)-positive, human epidermal growth factor receptor 2 (HER2)-negative breast cancer treated with combination palbociclib/letrozole who presented with hyperuricemia. In both cases, the patients experienced hyperuricemia and neutropenia that required palbociclib to be temporarily discontinued and its dose to be subsequently reduced. Although study data have demonstrated that combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Recovery from acute TLS with IV fluids and rasburicase 2019 Idrees et al [ 17 ] 48 Infiltrating ER + , PR + , HER2 − , p53 − , Ki67 10% carcinoma with bony and liver metastases No treatment had been given before TLS Bony and liver metastases Presentation with abdominal pain and oliguria. Found to be in spontaneous TLS from an as-yet undiagnosed breast cancer with widespread metastatic disease 2016 Bromberg et al [ 18 ] 78 Advanced, ER + , HER2 − ductal tumor Palbociclib/letrozole Widespread metastases Severe kidney injury resolved with intravenous fluids and allopurinol. Palbociclib dose reduced for ongoing treatment 2016 Bromberg et al [ 18 ] 86 Advanced, ER + , HER2 − ductal tumor Palbociclib/letrozole Liver metastases Developed hyperuricaemia was given allopurinol and encouraged to increase oral fluid intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovery from acute TLS with IV fluids and rasburicase 2019 Idrees et al [ 17 ] 48 Infiltrating ER + , PR + , HER2 − , p53 − , Ki67 10% carcinoma with bony and liver metastases No treatment had been given before TLS Bony and liver metastases Presentation with abdominal pain and oliguria. Found to be in spontaneous TLS from an as-yet undiagnosed breast cancer with widespread metastatic disease 2016 Bromberg et al [ 18 ] 78 Advanced, ER + , HER2 − ductal tumor Palbociclib/letrozole Widespread metastases Severe kidney injury resolved with intravenous fluids and allopurinol. Palbociclib dose reduced for ongoing treatment 2016 Bromberg et al [ 18 ] 86 Advanced, ER + , HER2 − ductal tumor Palbociclib/letrozole Liver metastases Developed hyperuricaemia was given allopurinol and encouraged to increase oral fluid intake.…”
Section: Discussionmentioning
confidence: 99%
“…Found to be in spontaneous TLS from an as-yet undiagnosed breast cancer with widespread metastatic disease 2016 Bromberg et al [ 18 ] 78 Advanced, ER + , HER2 − ductal tumor Palbociclib/letrozole Widespread metastases Severe kidney injury resolved with intravenous fluids and allopurinol. Palbociclib dose reduced for ongoing treatment 2016 Bromberg et al [ 18 ] 86 Advanced, ER + , HER2 − ductal tumor Palbociclib/letrozole Liver metastases Developed hyperuricaemia was given allopurinol and encouraged to increase oral fluid intake. Uric acid level reduced and palbociclib restarted at lower dose 2016 Baudon et al [ 19 ] 58 Invasive grade-III ductal carcinoma, ER − , PR − , HER2 − .…”
Section: Discussionmentioning
confidence: 99%
“…8 A total of 115 cases were reported between 1950 and February 2014. Eighteen cases of TLS occurring in breast cancer have been reported in the literature, 9-23 13 of which occurred in the context of systemic anticancer treatment. Twelve of these are written in English and were available to be reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve of these are written in English and were available to be reviewed. Bromberg et al 14 reported 2 cases of hyperuricaemia occurring in patients undergoing combination palbociclib/letrozole treatment, and suggest that one if not both of these cases may be presentations of TLS. A summary of all these cases, as well as 2 cases of spontaneous TLS in breast cancer 1011 and a case of TLS following hemibody irradiation 13 can be found in Table 2.…”
Section: Discussionmentioning
confidence: 99%